Cartilage Protective and Immunomodulatory Features of Osteoarthritis Synovial Fluid-Treated Adipose-Derived Mesenchymal Stem Cells Secreted Factors and Extracellular Vesicles-Embedded miRNAs - Enrico Ragni; Alessandra Colombini; Marco Viganò; Francesca Libonati; Carlotta Perucca Orfei; Luigi Zagra; Laura de Girolamo (Cells, 2021)
Intra-articular administration of adipose-derived mesenchymal stem cells (ASCs), either in vitro expanded or within adipose tissue-based products obtained at point-of-care, has gained popularity as innovative regenerative medicine approach for osteoarthritis (OA) treatment. ASCs can stimulate tissue repair and immunomodulation through paracrine factors, both soluble and extracellular vesicles (EV) embedded, collectively defining the secretome. Interaction with the degenerative/inflamed environment is a crucial factor in understanding the finely tuned molecular message but, to date, the majority of reports have described ASC-secretome features in resting conditions or under chemical stimuli far from the in vivo environment of degenerated OA joints. In this report, the secretory profile of ASCs treated with native synovial fluid from OA patients was evaluated, sifting 200 soluble factors and 754 EV-embedded miRNAs. Fifty-eight factors and 223 EV-miRNAs were identified, and discussed in the frame of cartilage and immune cell homeostasis. Bioinformatics gave a molecular basis for M2 macrophage polarization, T cell proliferation inhibition and T reg expansion enhancement, as well as cartilage protection, further confirmed in an in vitro model of OA chondrocytes. Moreover, a strong influence on immune cell chemotaxis emerged. In conclusion, obtained molecular data support the regenerative and immunomodulatory properties of ASCs when interacting with osteoarthritic joint environment.